The use of fibre reinforced crushed rocks for the improvement of tensile strength - Siripun, Komsun; Jitsangiam, Peerapong; Nikraz, Hamid (American Society of Civil Engineers (ASCE), 2011)
This study aims to report the possible use of fibre to improve the tensile strength of crushed rock base in a pavement in order to reduce the cracking of cemented material. As well is known, stabilized materials always present brittle responses under applied loads and suddenly collapse after peak loading. From this point, it means that cemented material only advances compressive behaviour and will never enhance long term performances such as fatigue and durability. Cemented crushed rock with fibre was selected to represent the tensile strength of pavement base material. Sophisticated tests were conducted to observe mechanical responses under applied loads such as indirect tensile and unconfined compressive strength, and the resilient modulus. The test results showed that fibre reinforcement improved the tensile strength and ductility of stabilized materials.